Предмет:
МатематикаАвтор:
аноним(х^2 + 3х) * (х^2 + 3х - 17) + 60 = 0;
введём новую переменную х^2 + 3х = у;
у(у - 17) + 60 = 0;
у^2 - 17у + 60 = 0;
D = b^2 - 4ac;
D = (-17)^2 - 4 * 1 * 60 = 289 - 240 = 49; √D = 7;
x = (-b ± √D)/(2a);
x1 = (17 + 7)/2 = 24/2 = 12;
x2 = (17 - 7)/2 = 10/2 = 5.
Выполним обратную подстановку:
1) х^2 + 3х = 12;
х^2 + 3х - 12 = 0;
D = 3^2 - 4 * 1 * (-12) = 9 + 48 = 57;
x1 = (-3 + √57)/2;
x2 = (-3 - √57)/2;
2) x^2 + 3x = 5;
x^2 + 3x - 5 = 0;
D = 3^2 - 4 * 1 * (-5) = 9 + 20 = 29;
x3 = (-3 + √29)/2;
x4 = (-3 - √29)/2.
Ответ. (-3 + √57)/2; (-3 - √57)/2; (-3 + √29)/2; (-3 - √29)/2.
Автор:
adónvo1dДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть